(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article provides Culture clash refers to conflicts arising from interactions between individuals with differing cultural values, beliefs, and practices. Such clashes can manifest in misunderstandings, stereotyping, and conflicts, particularly in multicultural settings like workplaces or schools. Effective management involves enhancing cultural awareness through education, promoting inclusive communication, and developing conflict resolution skills that respect cultural differences. Addressing these clashes constructively can enrich social interactions and foster inclusivity in increasingly diverse environments. This topic is crucial for enhancing cooperation and mutual respect across diverse cultural groups.